Clinical, Virological, and Immunological Findings in Patients with Toscana Neuroinvasive Disease in Croatia: Report of Three Cases - Tatjana Vilibic-Cavlek; Snjezana Zidovec-Lepej; Dragan Ledina; Samira Knezevic; Vladimir Savic; Irena Tabain; Ivo Ivic; Irena Slavuljica; Maja Bogdanic; Ivana Grgic; Lana Gorenec; Vladimir Stevanovic; et al. (Tropical Medicine and Infectious Disease, 2020)
Toscana virus (TOSV) is an arthropod-borne virus, transmitted to humans by phlebotomine sandflies. Although the majority of infections are asymptomatic, neuroinvasive disease may occur. We report three cases of neuroinvasive TOSV infection detected in Croatia. Two patients aged 21 and 54 years presented with meningitis, while a 22-year old patient presented with meningoencephalitis and right-sided brachial plexitis. Cerebrospinal fluid (CSF), serum, and urine samples were collected and tested for neuroinvasive arboviruses: tick-borne encephalitis, West Nile, Usutu, TOSV, Tahyna, and Bhanja virus. In addition, CSF and serum samples were tested for the anti-viral cytokine response. High titers of TOSV IgM (1000–3200) and IgG (3200−10,000) antibodies in serum samples confirmed TOSV infection. Antibodies to other phleboviruses (sandfly fever Sicilian/Naples/Cyprus virus) were negative. CSF samples showed high concentrations of interleukin 6 (IL-6; range 162.32−2683.90 pg/mL), interferon gamma (IFN-γ; range 110.12−1568.07 pg/mL), and IL-10 (range 28.08−858.91 pg/mL), while significantly lower cytokine production was observed in serum. Two patients recovered fully. The patient with a brachial plexitis improved significantly at discharge. The presented cases highlight the need of increasing awareness of a TOSV as a possible cause of aseptic meningitis/meningoencephalitis during summer months. Association of TOSV and brachial plexitis with long-term sequelae detected in one patient indicates the possibility of more severe disease, even in young patients.